Transmission and distribution electrical engineering - Bayliss, C. R. (Newnes, 2011)
This market leading classic is a true comprehensive on-the-job reference, covering all aspects of getting electricity from the source to user via the power grid. Electric power transmission and distribution is a huge sector, and engineers require the real world guidance of this book in order to upgrade networks to handle smart and renewable sources of power. This new edition covers renewable and distributed energy developments, international regulatory compliance issues with coverage of IEC standards, and new key conversions to US based standards and terminologies Utilising examples from real-life systems and challenges, this book clearly and succinctly outlines fundamental knowledge requirements for working in this area. Written by engineers for engineers, theory is tied to current best-practice, and new chapters cover hot topics including DC Transmission, Smart Networks and bringing renewable sources into the grid. Particularly useful for power engineers starting out on their career, this new edition ensures Bayliss remains an essential 'tool of the trade' for all engineers, technicians, managers and planners involved in electricity supply and industrial electricity usage.
Previous ed.: 2007.
Keywords: Electric power transmission.; Electric power distribution.; elektronické knihy; electronic books